Pengembangan Bahan Ajar Bermultimedia Interaktif dengan Discovery Learning pada Mata Pelajaran IPAS di Sekolah Penggerak - Wiwik Maladerita; Eri Barlian; Desyandri Desyandri; Azwar Ananda; Darmansyah Darmansyah; Ahmad Zikri (Universitas Negeri Padang, 2024)
In the era of the Fourth Industrial Revolution, the challenge in education is the integration of technology to develop interdisciplinary skills. Education 4.0 focuses on digital innovation in learning, preparing students for a rapidly changing and interconnected future. In Indonesia, the independent curriculum in Natural and Social Sciences (IPAS) accommodates self-directed learning, tailoring teaching to the diverse needs of students. This study employs the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to develop interactive multimedia teaching materials based on Discovery Learning for IPAS, aiming to enhance students' Higher Order Thinking Skills (HOTS). The research involved observations in five elementary schools in South Pesisir District, namely SDN 03 Malepang, SDN 14 Laban, SDN 03 Kampung Tangah in Bayang Subdistrict, SDN 16 Pasar Sungai Tunu, and SDN 09 Labuhan Tanjak. The results show the validity of natural science material at 3.58, language at 3.69, media at 3.50, and social science material at 3.50, all highly valid. The evaluation indicates an average respondent rating of 3.69, signaling high practicality. This research underscores the importance of interactive multimedia in effective and relevant education in the digital era, enhancing student engagement and understanding, and preparing them for future challenges.